Guessing Picture to Increase Students’ Speaking Skill in Speaking Class at Universitas Islam Madura - Yuliawati, Fitrah (Indonesian Journal Publisher, 2024)
The aim of this research is to improve students' speaking skills in speaking classes. This goal is based on a strong desire for students to be able to involve expressions and expand ideas in telling a picture. This research uses the classroom action research (CAR) method which consists of four steps, including: planning, implementation, observation and reflection. The data analysis used is a qualitative descriptive analysis technique. Criteria for success in this research is about increasing student's speaking ability at the third semester with an average completion score reaching 75%. Based on the results of the action, it can be concluded that student improvement with complete achievement. This is proven by the changes occurred from cycle I at 31.5%, cycle II at 52.6% and finally cycle III reached 78.9% which indicates that the student’s ability to tell stories has increased from previously not appearing to appear. This shows that image media can improve speaking ability to students in college.